Survival of overwintering nymphs of the small brown planthopper and its contribution to emergence timing - Keiichiro Matsukura; Sachiyo Sanada‐Morimura; Tomohisa Fujii; Masaya Matsumura; Takuya Shiba (Ecosphere, 2023)
Abstract This study developed a model for predicting the emergence timing of the first generation of the small brown planthopper, Laodelphax striatellus, by clarifying the effects of low temperature on survival and development of overwintering nymphs. In laboratory experiments, only temperatures below 0°C decreased nymph survival, although indirect chilling injury began to occur at about 4°C. No nymphs survived for longer than 7 days at −4°C. The developmental zero of overwintering nymphs was estimated to be 5.18°C. A model developed based on these survival and development parameters accurately predicted the distribution and emergence timing of the first generation of L. striatellus in the Kyushu region of Japan. Under future climate conditions predicted by the HadGEM2‐ES and MRI‐CGCM3 climate models under the RCP2.6 and RCP8.5 projections, L. striatellus is expected to show range expansion and advancement of emergence timing, although the degree of change varies among models and projections. Gaining a precise understanding of the overwintering biology of insect pests such as L. striatellus will help us accurately evaluate and predict future risks to crops under climate change.